Prognostic marker Musashi-2 modulates DNA damage response and radioresistance in diffuse large B-cell lymphoma - Habig, Timo; Reichstein, Lasse; Brücksken, Kathrin A.; Sicking, Mark; Labisch, Jan; Oertel, Michael; Korsching, Eberhard; Lenz, Georg; Hailfinger, Stephan; Greve, Burkhard; Troschel, Fabian M.; Eich, Hans Theodor (Frontiers in Cell and Developmental Biology, 2025)
IntroductionTreatment resistance is a major hurdle in diffuse large B-cell lymphoma (DLBCL) therapy. Here, we assessed the relevance of the Musashi (MSI) RNA-binding protein family for DLBCL treatment efficacy. As important gene expression regulators, these proteins have previously been associated with tumorigenesis, treatment failure, and reduced survival in other malignancies, making them promising candidates for assessment in the context of DLBCL outcome and therapy resistance.MethodsWe first leveraged publicly available gene expression studies to determine expression and prognostic relevance of MSI1 and MSI2 in DLBCL. We then characterized MSI2 co-expressed therapy-relevant signaling. After performing MSI2 knockdown experiments we investigated subsequent effects on DLBCL gene expression in vitro using qPCR, Western blot, protein arrays, and flow cytometry. Finally, cell viability assays and clonogenic assessments were used to assess resistance to radiation, vincristine, and doxorubicin chemotherapy.ResultsMSI2 was overexpressed and prognostically unfavorable in univariable and multivariable analyses in DLBCL while MSI1 showed very low expression. High MSI2 expression was associated with increased stemness and DNA repair signaling. MSI2 knockdown led to a loss of stemness-associated markers and compromised DNA repair protein activation while increasing radiation-induced DNA double-strand break levels. Cell survival after either radiotherapy, vincristine or doxorubicin chemotherapy was impaired after MSI2 knockdown in follow-up analyses, suggesting a radio- and chemosensitizing effect.DiscussionWe propose that MSI2, a prognostic marker, may modulate the susceptibility of DLBCL towards genotoxic therapy. Suppressing MSI2 may hold promise to sensitize DLBCL to DNA-targeted treatment.